Effect of Web-Based Early Diagnosis of Dental and Oral Diseases with Validity Level of Dentist Final Diagnosis in Public Health Center, Makassar, Indonesia - Masriadi1, Dolly Indra2, Harlinda2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background. One of the organs of the body that is lacking attention is the teeth and mouth, whereas maintaining healthy teeth and mouth is very important, because the nerves of the teeth are related and directly affect the nerves of other organs. The development of information technology that is so advanced has entered the world of health, namely to detect early dental and oral diseases by using an expert system. Making an expert system is not to replace the expert itself but can be used as a very experienced assistant. There is a need to solve this problem so that people can know how to deal with diseases related to teeth and mouth. The various information supporting factors in this study by building an expert system with three methods are Certainty Factor (CF), Dempster Shafer (DS) and Bayes Theorem to diagnosis early dental and oral disease events and determine the effect of expert systems in increasing the validity level of dentist diagnosis. Material and Method The type of research used was an observational method in a cross-sectional study design. The sampling method uses total sampling. The study was conducted in September-January 2020. The number of sampling was 200 people. This research consists of three stages are the making of an application system, application testing, and the final stage is a statistical test. The data analysis technique used in this study is Chi-square and validity test. Results. The results of the analysis of the relationship between the value of accuracy with the validity of the doctor’s diagnosis found variable diagnosis doctor have p value (0.013), DS value, CF and Bayes Value are the same p (0,000) <p (0.05). Conclusion. Applications built using the CF, DS and Bayes Theorem methods can be used by users to detect dental disease early before making further examinations to a specialist. The test results given by the system are the same as the results given by experts (dentists). The system of early diagnosis of dental and oral diseases has a very significant effect on the level of validity of the dentist final diagnosis.